Best Practices of Digital Transformation in M&A and Divestitures for Small- and Medium-Sized Organizations - Gutti, Sreeram (Digital Repository of Theses - SSBM Geneva, 2025)
Mergers, Acquisitions, and Divestitures are the driving forces of change and growth in the business world. The business transformations in the context of mergers and acquisition (M&A) are complex, resource intensive, involve multi organizations, teams, optimization and convergence of workflow processes, IT systems, and cultures. The M&A business decision outcomes such as strengthening competitive position by developing the new capabilities, increasing sales and profits, capitalizing on potential opportunities after merger takes extended period to realize the benefits. The M&A integration execution needs to be orchestrated by leveraging the strategic and tactical means within the rigid timelines of transfer services agreement (TSA). Digital transformation solutions that enable and empower the integration process need thorough attention from the early phases of M&A planning and integration. The thesis aims to provide a modular structure, M&A priorities, and the best transformation practices for M&A technology practitioners and management practitioners. Thesis aims to provide an end-end view of the M&A journey, building blocks of understanding M&A, areas of focus leading to the solution selection till post-merger integration. The current thesis aims to provide applicable best practices at different phases of M&A journey that can be applied to any industry segment so a practitioner can apply to any real-time situation of M&A integration. Research provides a modular view of business transformation and the building blocks that influence the transformation journey. To highlight the best practices of digital transformations, it is imperative to consider the lifecycle of the M&A, establish key priorities for each stakeholder to help facilitate the decision-making prior to embarking on the journey of integration Thesis will try to leverage the industry’s best practices and provide the required knowledge to experienced or inexperienced M&A technology professionals to take a broader view and dive into the details to provide strong foundation and direction to make decisions. The thesis will focus on the boundaries of technology due diligence, technology solutions and post-merger integration best practices. The types of mergers, acquisitions, valuations of the companies, value drivers for mergers, and influencing factors such as compliance and legal requirements, objectives of mergers for a given situation will be researched and presented from the perspective of the business context. Literature reviews paved the path to finalize broader areas of research to structure the best practices of transformation in M&A. The broader domains which act as pillars of this thesis are • Business Context • M&A Priorities that Influence Digital Transformations • Buyer IT Assessment • Seller IT Assessment • Due Diligence during Deal Planning • Due Diligence post Deal closure • Finalize Digital Transformation Solutions • PMI - Post-Merger Integration The research journey focused on the identification of experts who have firsthand experience in leading M&A. The expectation from the experts has been to challenge the premise, provide deep perspectives in interviews, highlight industry’s best practices, high risks, risk remediation solutions, provide scoring for specific questions and provide feedback on the best practices or models developed as a part of the journey. Another expectation from experts was to prioritize the topics during the discussions that influence business decisions and digital transformation technical solution decisions in M&A. The research method used to reach conclusions is a hybrid approach with quantitative and qualitative analysis by interviewing experienced finance and IT professionals. Extensive effort has gone into structuring the questions with various stakeholders to capture the responses with scores to perform quantitative analysis. Interviews and data analysis provided the required directions to carve out the best practices for digital transformations in M&A. The business context can be attributed to foundational aspects of M&A which act as the business premise for other research focus areas. Business context helps in identifying the M&A priorities for any M&A transaction, the M&A priorities eventually influence the digital transformation decisions. Business context provides the magnitude of the M&A transaction and scale of planning required for M&A integration. Understanding the organizational maturity of the seller and buyer companies from the perspective of IT governance and IT Platform maturity will play an important role in making the digital transformation solution decisions. To make an offer to buy a company, the buyer needs to perform thorough due diligence during the decision-making process to ensure the buying organization's strategic and financial objectives are achieved. Due diligence will be an iterative process from the initial evaluation during deal planning with limited time restrictions. IT readiness of the buying and selling organizations is evaluated through SWOT (strengths, weaknesses, opportunities, threats) analysis of their respective IT platforms and IT governance maturity. Modeling iterative due diligence to make key decisions, carving out the transformation and integration strategy with a focus on schedule and budgets is important. Taking all the above aspects into consideration, the solutions required for the transformation are finalized keeping cost, risk appetite, situation dynamics, leadership support into perspective. Finally completing the post-merger integration provides a closure for the Digital Transformation journey for M&A. M&A is a business transformation achieved through digital transformation solutions. While the objective of research is to identify the best practices in digital transformations in M&A, a life cycle phased approach of M&A is taken into consideration. The objective of my research is to provide the best transformation practices model for M&A technology practitioners, integrators across various industry verticals to view the M&A from lifecycle perspective and identify the best practices at different stages of the M&A that will provide guidance for the digital transformation integration of both entities.